2017
DOI: 10.1007/s10530-017-1396-2
|View full text |Cite
|
Sign up to set email alerts
|

Space invaders: effects of invasive alien Pallas’s squirrel on home range and body mass of native red squirrel

Abstract: Alien species can affect native species through several ecological processes such as competition. Here we tested the hypothesis of interspecific competition for space and food resources between the native Eurasian red squirrel and the invasive Pallas’s squirrel introduced in Italy. We used an experimental study design comparing space and habitat use and body condition parameters of red squirrels between areas of co-occurrence with the Pallas’s squirrel and areas without it. There were no differences in mean ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…High food availability also attracts the presence of the native squirrel, which has a similar diet [62,64]. The observed aggregation between these two squirrels is noteworthy, because previous studies have reported the competitive exclusion of native squirrels by introduced ones [109,110]. However, we focused on two species of squirrels with different habitats (the Mexican red-bellied squirrel is predominantly arboreal and the rock squirrel is clearly saxicolous) and found that both seem to benefit from the same type of vegetation patches within our study area.…”
Section: Discussionmentioning
confidence: 99%
“…High food availability also attracts the presence of the native squirrel, which has a similar diet [62,64]. The observed aggregation between these two squirrels is noteworthy, because previous studies have reported the competitive exclusion of native squirrels by introduced ones [109,110]. However, we focused on two species of squirrels with different habitats (the Mexican red-bellied squirrel is predominantly arboreal and the rock squirrel is clearly saxicolous) and found that both seem to benefit from the same type of vegetation patches within our study area.…”
Section: Discussionmentioning
confidence: 99%
“…In these two European countries, researchers and citizens have reported a lower number of red squirrel observations, mainly at the periphery of the area on which Pallas's squirrels have become established. In Italy, Mazzamuto and coworkers specifically described the competition mechanism between Pallas's squirrels and Eurasian red squirrels and the outcome of interspecific interactions [102,111]. The native and invasive species have a high degree of niche overlap and compete for space and food resources [111].…”
Section: Harm To Native Speciesmentioning
confidence: 99%
“…In Italy, Mazzamuto and coworkers specifically described the competition mechanism between Pallas's squirrels and Eurasian red squirrels and the outcome of interspecific interactions [102,111]. The native and invasive species have a high degree of niche overlap and compete for space and food resources [111]. Red squirrels, when in cooccurrence with the IAS, are distributed in patches and increase the intraspecific space overlap up to three times [111].…”
Section: Harm To Native Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…About 250 squirrel introduction events by at least 20 species have occurred in the last 150 years (Bertolino, ; Bertolino & Lurz, ), most of which have been successful (Bertolino, ). The impacts of alien squirrels range from competitive exclusion of native species (Gurnell, Wauters, Lurz, & Tosi, ; Mazzamuto, Morandini, et al, ), to tree debarking (Kuo, ; Mayle, Proudfoot, & Poole, ; Mori, Mazzoglio, Rima, Aloise, & Bertolino, ), and parasite/disease transmission (Marsot et al, ; Romeo et al, ; Tompkins, Sainsbury, Nettleton, Buxton, & Gurnell, ).…”
Section: Introductionmentioning
confidence: 99%